Pengaruh Media Pembelajaran Berbasis Powerpoint terhadap Motivasi Belajar Siswa SMA Katolik Don Bosco Lembean - Marianus Muharli Mua; Kenshi Leonard Solung (Sekolah Tinggi Pastoral Don Bosco Tomohon, 2023)
This paper is the result of a review of research conducted at Don Bosco Lembean Catholic High School by measuring how much influence the use of powerpoint-based learning media has on students' learning motivation. The method used is a quantitative research method. The results of the study found that the use of PowerPoint-based learning media at Don Bosco Lembean Catholic High School obtained a score of 0.80 so it was in the VERY GOOD category. The learning motivation of Don Bosco Lembean Catholic High School students obtained a score of 0.80 so it was in the VERY GOOD category. Judging from the results of a simple linear regression analysis, the value of the coefficient of determination (R square) which is a measure of how much influence PowerPoint-based learning media has as a variable X on variable Y, namely student learning motivation at Don Bosco Lembean Catholic High School is 0.440 with a significance of 0.000. PowerPoint learning media contributes 44% to student motivation at Don Bosco Lembean Catholic High School and 56% is influenced by other factors.